Bivalent Vaccine Effectiveness Against Anal Human Papillomavirus Positivity Among Female Sexually Transmitted Infection Clinic Visitors in the Netherlands. (23rd April 2019) - Woestenberg, Petra J; King, Audrey J; Van Benthem, Birgit H B; Leussink, Suzan; Van der Sande, Marianne A B; Hoebe, Christian J P A; Bogaards, Johannes A; ,
Abstract: Human papillomavirus (HPV) vaccines are indicated for anal cancer prevention, but evidence for vaccine effectiveness (VE) against anal HPV infections among women is limited. We estimated the VE (≥1 dose) against anal HPV positivity of the bivalent vaccine, whose target types HPV-16/18 are associated with approximately 90% of HPV-related anal cancers. Among 548 female STI clinic visitors 16–24 years old who provided an anal swab sample as part of a repeated cross-sectional survey, VE against HPV-16/18 was 89.9% (95% confidence interval, 63.0%–97.2%). Type-specific VE correlated well with VE against cervicovaginal HPV (Spearman ρ = 0.76), suggesting comparable effectiveness of HPV-16/18 vaccination against genital and anal infections. Abstract : This study shows high vaccine effectiveness of the bivalent human papillomavirus (HPV) vaccine against anal HPV positivity, especially HPV-16/18. Type-specific effectiveness correlated well with effectiveness against cervicovaginal HPV positivity, suggesting comparable protection of HPV-16/18 vaccination against anal and genital infections.